2012
DOI: 10.1108/14635781211256756
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure decisions of LPTs in a small economy

Abstract: PurposeThe existing literature on real estate investment trust (REIT) capital‐structure decisions implicitly excludes either interest payment tax shield benefits or a trust's growth potential. The purpose of this paper is to test the long‐term debt leverage decisions of listed property trusts (LPTs), but without excluding interest payment tax shield benefits and growth potential. A new variable, the exchange rate, is included in the tests, because financial products subject to globalization, such as SWAPs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…They also found that non-REIT companies were significantly more leveraged than REITs. In New Zealand and Australia, the research about capital structure in NZ LPTs was done by Dong (2012). In this study, trade-off theory was followed by the NZ LPTs, and the exchange rate of NZ dollar was estimated to be explaining the capital structure of NZ PLTs significantly.…”
Section: Literature Of Property Firms' Financial Behaviourmentioning
confidence: 99%
“…They also found that non-REIT companies were significantly more leveraged than REITs. In New Zealand and Australia, the research about capital structure in NZ LPTs was done by Dong (2012). In this study, trade-off theory was followed by the NZ LPTs, and the exchange rate of NZ dollar was estimated to be explaining the capital structure of NZ PLTs significantly.…”
Section: Literature Of Property Firms' Financial Behaviourmentioning
confidence: 99%
“…With regard to capital structure, REITs as public should also raise capital to finance its operation. Study from (Dong, 2012) found that Listed Property Trusts (LPTs), name for REITs in New Zealand, tend to reduce long-term debt in its capital structure when there is appreciation on New Zealand dollar one-year forwards rate because it will favour LPTs to get short-term debt overseas with foreign currency, thus shrinking long-term debt leverage. However, REITs with high market valuation tend to have persistent and high leverage (Feng, Ghosh, & Sirmans, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…However, existing literature has confirmed that fundamental business factors should determine REITs' optimal as-set composition, income composition, and leverage ratio. These factors include market price (Chan et al, 2005), asset liquidation value (Giambona et al, 2008;Danielsen et al, 2014), market-to-book value (Feng et al, 2007), financing cost and risk (Ooi, 1999;Sha et al, 2020), global fund flow (Dong, 2012), and economic circle (Lee et al, 2016;Ruddock & Ruddock, 2014). Thus, REITs are motivated to use EM approaches to trim their financial reports to fit REIT regulations.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%